Atomic force microscopy as a tool in asphalt research - García , Adriana (2025)
The Atomic Force Microscope is used to obtain superficial images with high resolution. As well, to acquire information about the mechanical properties of a material. This tool has several operation modes, such as static, dynamic, tapping and contact, among others. It is worth to mention that cantilever has several geometries, then choosing the right one is a crucial step in any investigation that uses AFM. The focus of this article is to give a broad outlook of the AFM, from its operation modes to its applications in asphalt studies. Upon this article, the AFM is highly used in asphalts to analyse the microscopic properties and to understand how these properties impact its macroscopic performance.